The Construction of Academic Staff Identity Following The Conversion From Ikip to University - *, Faridah (Sebelas Maret University, 2016)
This paper discussed the construction of academic staff identity following the conversion in 1999, from IKIP Ujung Pandang to Universitas Negeri Makassar (UNM), South Sulawesi, Indonesia. It examined how the idea of becoming a university was perceived by university members and how it shaped the undergraduate program for teacher education at the university. Interviews were conducted to academic staff who had been working at the university before and after the conversion. The findings revealed that the meaning of becoming a university had shaped the changing characteristics of IKIP as a teacher education institute. The importance of disciplinary knowledge that characterised university, had strongly driven the scheme of the teacher education program. It also shaped the role of academic staff, as well as their professional careers. In order to be recognised as a university, the academic staff had been driven and constructed to fit the university features established by the government of Indonesia. For UNM, the strategy to strengthen academic staff qualifications in the field of disciplinary knowledge has turned these âteacher educatorsâ into âuniversity lecturersâ. This qualification becomes the certificate of recognition for them as university lecturers, not as teacher educators only. It was argued that it had created identity issues for teacher educators, especially in the aspect of their academic expertise.